Pharmacogenomic Testing in Psychiatry: Ready for Primetime?. Issue 2 (February 2020) - Rakesh, Gopalkumar; Sumner, Calvin R.; Alexander, Jeanne Leventhal; Gross, Lawrence S.; Pine, Janet; Slaby, Andrew; Garakani, Amir; Baron, David
Abstract : Abstract: Pharmacogenomic testing in clinical psychiatry has grown at an accelerated pace in the last few years and is poised to grow even further. Despite robust evidence lacking regarding efficacy in clinical use, there continues to be growing interest to use it to make treatment decisions. We intend this article to be a primer for a clinician wishing to understand the biological bases, evidence for benefits, and pitfalls in clinical decision-making. Using clinical vignettes, we elucidate these headings in addition to providing a perspective on current relevance, what can be communicated to patients, and future research directions. Overall, the evidence for pharmacogenomic testing in psychiatry demonstrates strong analytical validity, modest clinical validity, and virtually no evidence to support clinical use. There is definitely a need for more double-blinded randomized controlled trials to assess the use of pharmacogenomic testing in clinical decision-making and care, and until this is done, they could perhaps have an adjunct role in clinical decision-making but minimal use in leading the initial treatment plan.